NOx/SOx Emissions and Carbon Abatement - Complainville, Christophe (OECD Economics Department Working Papers, 1994)
This paper provides evidence on the reductions of NOx/SOx emissions induced by the adoption of carbon abatement policies. It describes the methodology to compute emissions of these pollutants and the way they were introduced in the OECD GREEN model. This required a compromise between the "top-down" structure of the model and the very detailed information that, in principle, is required to compute NOx/SOx emissions. The simulation results suggest that, on average, the reductions relative to Baseline levels of NOx/SOx emissions may be in the same order of magnitude or are higher than the abatement imposed on carbon emissions ...